Sędziwi ojcowie – Laertes i Priam w epopejach Homera - Stępniewska, Alicja (Vox Patrum, 2011)
Subject of the article are experience and sufferings two fathers – Laertes, King of Ithaca and Priam, King of Troy. They both had that experience in its old age, but in different dimension. Son of the first of fathers – Odys has disappeared without tidings, but he came back to Ithaca after twenty years of wandering, to the great joy of longing father. The son of the second of fathers – Hector was killed in a duel with Achilles. The aged Priam in difficult conversation with his son’s killer is reminding Achilles the suffering of his aged father Peleus, who is living in loneliness, to break heart of Achilles. Due to well-aimed arguments, particularly adduction for the feckless old age of the father, aged Priam reaches intentional point – gets corpse of his son back.